2015
DOI: 10.1073/pnas.1502522112
|View full text |Cite
|
Sign up to set email alerts
|

The maize disease resistance gene Htn1 against northern corn leaf blight encodes a wall-associated receptor-like kinase

Abstract: Northern corn leaf blight (NCLB) caused by the hemibiotrophic fungus Exserohilum turcicum is an important foliar disease of maize that is mainly controlled by growing resistant maize cultivars. The Htn1 locus confers quantitative and partial NCLB resistance by delaying the onset of lesion formation. Htn1 represents an important source of genetic resistance that was originally introduced from a Mexican landrace into modern maize breeding lines in the 1970s. Using a high-resolution map-based cloning approach, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
221
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(245 citation statements)
references
References 33 publications
9
221
0
1
Order By: Relevance
“…Recognition of OGs by the WAK PRRs is followed by the activation of a classic biotrophic defense response ( 20 ). Recent research has implicated WAK genes in conferring resistance to the maize diseases head smut, caused by the soil-borne biotrophic fungus Sporisorium reilianum ( 21 ), and northern corn leaf blight, caused by the hemibiotrophic fungus Exserohilum turcicum ( 22 ). The mechanisms of pathogen detection for these WAK resistance genes are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of OGs by the WAK PRRs is followed by the activation of a classic biotrophic defense response ( 20 ). Recent research has implicated WAK genes in conferring resistance to the maize diseases head smut, caused by the soil-borne biotrophic fungus Sporisorium reilianum ( 21 ), and northern corn leaf blight, caused by the hemibiotrophic fungus Exserohilum turcicum ( 22 ). The mechanisms of pathogen detection for these WAK resistance genes are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies in maize showed that WAK played an important role in response to head smut soil-borne disease caused by fungus Sporisorium reilianum (Zuo et al, 2015) and northern corn leaf blight caused by fungus Exserohilum turcicum (Hurni et al, 2015). One WAK gene was detected in the AB4.1 region under selection for AB resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the WAK gene plays critical roles in cell expansion, pathogen resistance, and heavy-metal stress tolerance in Arabidopsis [51]. Hurni et al [52] isolated northern corn leaf blight resistance gene Htn1 that encodes WAK in maize. These candidate genes provide a basis for dissecting the genetic mechanism of WSC and will be useful in further investigations of the various functions of WSC in wheat.…”
Section: Discussionmentioning
confidence: 99%